URGENSI PENGELOLAAN RUANG TERBUKA HIJAU (RTH) PUBLIK DI KOTA BOGOR DALAM PERSPEKTIF GOOD ENVIRONMENTAL GOVERNANCE - Kania Winiastari; martini Martini (Journal of Politic and Government Studies, 2026)
Public Green Open Space (RTH) plays an important role in supporting environmental quality and the social needs of urban communities. In Bogor City, the distribution of public RTH still shows inequality among regions, resulting in unequal access to and benefits from green open spaces. This study aims to analyze the management of public RTH in Bogor City from the perspective of Good Environmental Governance (GEG), with a focus on management and equitable access to public RTH. 1Mahasiswa Ilmu Pemerintahan Universitas Diponegoro 2Dosen Ilmu Pemerintahan Universitas Diponegoro 1 This study employed a descriptive qualitative approach using semi-structured interviews and documentation techniques. The informants consisted of Civil Servants (ASN) from the Bogor City Housing and Settlement Agency and members of the community who utilize public RTH. The results show that the management of public RTH already has regulatory foundations, institutional structures, and management mechanisms that support the provision of RTH. However, the implementation of Good Environmental Governance principles has not fully supported equitable access to RTH across regions. The distribution of public RTH remains uneven among districts, and its management is still oriented toward administrative and technical aspects. This study concludes that the management of public RTH in Bogor City has not fully supported equitable access to green open spaces for the community.